Redefinisi Identitas Diri Anak Binaan Lembaga Pembinaan Khusus Anak - Renda, Trijuliani; Pellondou, Andri Oktovianus; Nalle, Imin Yustri (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to examine how foster children redefine their self-identity after being fostered at the Special Children’s Development Institution. The method used in this study is a qualitative method with a sociological research type. In this study, the researcher used Peter Berger's social construction theory to examine the process of constructing the self-identity of foster children and George Herbert Mead's theory to examine how interaction through symbols affects the process of redefining the self-identity of foster children. The results of the study: first, Dialectics in the social environment of the Special Children’s Development Institution defines children's self-identity with values ​​instilled in thought patterns and actions, second, self-awareness is formed through spiritual guidance which then helps foster children define themselves, third, fulfillment of physical, spiritual needs, assistance, attention, protection and support from the social environment and parents in the foster institution makes foster children aware of the limitations in interacting with others.